Cerebral Amyloid Angiopathy-related Inflammation Presenting With a Cystic Lesion in Young-onset Alzheimer Disease. (July 2021) - Ringman, John M.; Joe, Elizabeth; Sheikh-Bahaei, Nasim; Miller, Carol; Vinters, Harry V.; Guzman, Samuel; Chui, Helena C.
Abstract : We describe a patient with cerebral amyloid angiopathy-related inflammation (CAA-ri) presenting as Alzheimer disease (AD) with a mass lesion with symptom onset at age 59. He was found to have a nonenhancing lesion in the right temporal lobe on magnetic resonance imaging without evidence of hemorrhage. He underwent a biopsy which showed amyloid beta in blood vessel walls and a perivascular inflammatory infiltrate consistent with CAA-ri. Neurofibrillary tangles were present and a flortaucipir positron emission tomography showed bilateral signal highest in the lateral temporal and parietal cortices. A lumbar puncture showed tau, p-tau, and amyloid beta levels consistent with AD without evidence of inflammation. He was homozygous for the APOE ε4 allele. He died at age 67. A focus of CAA-ri can be present in the context of AD with a mass lesion and without evidence of hemorrhage, significant ischemic changes, or overt inflammation on cerebrospinal fluid examination.